Expansin-related proteins: biology, microbe–plant interactions and associated plant-defense responses. Issue 11 (2nd December 2020) - Narváez-Barragán, Delia A.; Tovar-Herrera, Omar E.; Segovia, Lorenzo; Serrano, Mario; Martinez-Anaya, Claudia
Abstract : Expansins, cerato-platanins and swollenins (which we will henceforth refer to as expansin-related proteins) are a group of microbial proteins involved in microbe-plant interactions. Although they share very low sequence similarity, some of their composing domains are near-identical at the structural level. Expansin-related proteins have their target in the plant cell wall, in which they act through a non-enzymatic, but still uncharacterized, mechanism. In most cases, mutagenesis of expansin-related genes affects plant colonization or plant pathogenesis of different bacterial and fungal species, and thus, in many cases they are considered virulence factors. Additionally, plant treatment with expansin-related proteins activate several plant defenses resulting in the priming and protection towards subsequent pathogen encounters. Plant-defence responses induced by these proteins are reminiscent of pattern-triggered immunity or hypersensitive response in some cases. Plant immunity to expansin-related proteins could be caused by the following: (i) protein detection by specific host-cell receptors, (ii) alterations to the cell-wall-barrier properties sensed by the host, (iii) displacement of cell-wall polysaccharides detected by the host. Expansin-related proteins may also target polysaccharides on the wall of the microbes that produced them under certain physiological instances. Here, we review biochemical, evolutionary and biological aspects of these relatively understudied proteins and different immune responses they induce in plant hosts.